USING GIS TO DETERMINE THE ENERGY OF RELIEF. PATTERN MODULE METHOD (PANGEEA, 2025)
Geographic information systems allow the development of varied and complex maps and analyzes of geographic components. The quantitative and qualitative results of these analyzes find use in the most varied fields ranging from road and railway systems to land and forest landscaping.
Keywords: G.I.S.; energy of relief; S.R.T.M.90; D.E.M; Stereo70; georeferencing; morphometry; Iara